DOP11 Normalisation of faecal calprotectin within 12 months of diagnosis is associated with a reduced risk of disease progression in Crohn's disease. (15th January 2020) - Plevris, N; Fulforth, J; Jenkinson, P; Lyons, M; Chuah, C; Siakavellas, S; Pattenden, R; Arnott, I; Jones, G; Lees, C
Abstract: Background: Faecal calprotectin (FC) demonstrates an excellent correlation with endoscopic inflammation. In addition, a treatment-decision algorithm for Crohn's disease (CD) incorporating FC outperforms and improves 12-month mucosal healing compared with a strategy based on symptoms alone. The aim of this study was to determine whether normalisation of FC (<250 μg/g) within 12-months of diagnosis is associated with a reduction in disease progression in CD. Methods: This was a retrospective cohort study performed at a tertiary IBD centre. All incident cases of CD diagnosed between 2005 and 2017 were identified. Patients with an FC measurement of >250 μg/g at diagnosis who also had at least 1 follow-up FC measured within the first 12-months of diagnosis and >12 months of follow-up were included. The primary endpoint was a composite of progression in Montreal disease behaviour (B1 to B2/3 or B2 to B3 or new perianal disease), surgery or hospitalisation. Results: A total of 375 patients were included with a median follow-up of 5.3 years (IQR 3.1–7.4). Normalisation of FC (<250 μg/g) within 12 months of diagnosis was confirmed in 43.5% ( n = 163/375) of the cohort. On multivariable Cox-proportional hazards regression analysis, individuals who normalised their FC within 12 months of diagnosis had a significantly lower risk of composite disease progression (HR 0.351, 95% CI 0.235–0.523, p < 0.001) (Figure 1). Cumulative rates of composite disease progression were 7.8%, 21.4% and 29.9% in those that normalised their FC vs. 22.8%, 50.7% and 60.5% in those that did not at 2, 5 and 7 years after diagnosis, respectively. In addition, normalisation of FC was the only predictor that remained significant for all the separate progression end-points (progression in Montreal behaviour / new perianal disease: HR 0.250, 95% CI 0.122–0.512, p < 0.001; hospitalisation: HR 0.346, 95% CI 0.217–0.553, p < 0.001; surgery: HR 0.370. 95% CI 0.181–0.755, p = 0.006). The strongest predictor of whether an individual normalised their FC within 12 months was the commencement of a biologic within 3 months of diagnosis (OR 4.288, 95% CI 1.585–11.0601, p = 0.004). Conclusion: Normalisation of FC by 12-months of diagnosis is associated with a reduced risk of disease progression in CD. Our data provide strong support for implementation of treat-to-target strategies earlier than previously tested in Crohn's disease. The immediate implication for healthcare providers and patients is that by ensuring resolution of mucosal inflammation - measured by proxy with faecal calprotectin, and regardless of other variables - within 1 year of diagnosis has a dramatic effect on disease course.